2021
DOI: 10.1016/j.jtocrr.2021.100249
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Evaluation of Atezolizumab Plus Platinum-Etoposide Chemotherapy in Patients With Extensive-Stage SCLC in Canada

Abstract: Introduction The real-world data evaluating treatment outcomes of atezolizumab plus carboplatin-etoposide chemotherapy (atezolizumab) for extensive-stage SCLC (ESCLC) are lacking. Our objective was to evaluate real-world outcomes of ESCLC treated with atezolizumab. Methods A retrospective analysis of provincial patients with ESCLC who started first-line (1L) systemic treatment was conducted. We primarily evaluated the progression-free survival (PFS) and overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“… 24 Actually, similar outcomes to those in the present study have been observed in recent retrospective observational studies of chemoimmunotherapy for lung cancer. 25 , 26 , 27 Collectively, these results suggest comparable outcomes to those in clinical trials, while safety is somewhat inferior in clinical practice settings in which patients with lung cancer receive chemoimmunotherapy. However, the external validity of previous clinical trial results could not be fully investigated in these previous retrospective studies, as patients who met the eligibility criteria of clinical trials were expected to have similar outcomes to those in pivotal clinical trials, even in clinical practice settings.…”
Section: Discussionmentioning
confidence: 68%
“… 24 Actually, similar outcomes to those in the present study have been observed in recent retrospective observational studies of chemoimmunotherapy for lung cancer. 25 , 26 , 27 Collectively, these results suggest comparable outcomes to those in clinical trials, while safety is somewhat inferior in clinical practice settings in which patients with lung cancer receive chemoimmunotherapy. However, the external validity of previous clinical trial results could not be fully investigated in these previous retrospective studies, as patients who met the eligibility criteria of clinical trials were expected to have similar outcomes to those in pivotal clinical trials, even in clinical practice settings.…”
Section: Discussionmentioning
confidence: 68%
“… 10 In a retrospective data analysis, chemotherapy plus atezolizumab for patients with ES-SCLC with a PS of more than or equal to 2 was reported to be feasible; however, the OS was short, which is consistent with our present observations. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, three patients from group A developed radiation pneumonitis, which was classified as grade 2 in two patients and grade 1 in one patient. [5,6], and two recent real-world evaluations [8,9]. The median PFS and OS for the IMpower 133 study were 5.2 and 12.3 months, respectively [5].…”
Section: Subgroup Analysis Based On Radiation Treatmentmentioning
confidence: 99%
“…To our knowledge, only two real-world studies have confirmed the beneficial effects of adding atezolizumab to chemotherapy in the treatment of ES-SCLC [8,9]. Given this paucity of data, we believe that the evaluation of retrospective data may help further evaluate immunotherapy in patients with ES-SCLC.…”
Section: Introductionmentioning
confidence: 99%